SHI irradiation induced effects in functionalized MWCNTs - Saikiran, V.; Pathak, A. P.; Rao, N. Srinivasa; Devaraju, G.; Debgupta, Joyashish; Kyriakou, I.; Emfietzoglou, D. (Radiation Effects and Defects in Solids, 2012)
Multi-walled carbon nanotubes (MWCNTs) have attracted extensive attention globally due to their applications in modern nanotechnology. It is very important to study the effects on these MWCNTs under swift heavy ion (SHI) irradiation since ion irradiation has been recognized as one of the best tools for nanostructuring of materials, in general. Here, we present the effects of 80MeV Ni ions with a fluence ranging from 3 x 10(12) to 3 x 10(13) ions/cm(2) on functionalized MWCNT mats. The properties of pristine and irradiated samples were studied using X-ray diffraction, Raman spectroscopy and transmission electron microscopy. The effects of SHI irradiation on these samples are discussed in detail.
Keywords: CNT; Raman; SHI; TEM